A System-Wide Model for Solid Waste Separation and Food Waste Discharge to Sewer Systems - Angula, Shalongo (Department of Civil Engineering, 2023)
The emergence of the circular economy, together with the changing paradigms in resource and environmental management, has resulted in a call to (1) convert wastewater treatment plants (WWTPs) to water resource recovery facilities (WRRF) and (2) diversion of organic waste (i.e., food waste) from landfills. Due to excess anaerobic digester (AD) capacities at most WWTPs, it has been proposed to co-digest sewage sludge and food waste in the AD at WWTPs to enhance resources (mainly energy and nutrient) recovery. However, suitable options for sustainable food waste handling (i.e., separation and transport) and the characteristics of food waste have not been established, particularly in South Africa. Without characterising food waste, it is impossible to include it in WWTP simulation models. In this study, food waste and sewage sludges were limited to the household food waste and primary sludge categories, respectively. A detailed review on alternative sustainable solid waste separation and food waste transport systems was carried out and a review paper was submitted to Environmental Challenges journal for publication. The experimental investigation of the study focused on identifying the biodegradable organic composition of selected substrates, i.e., primary sludge (PS), food waste, and PS and food waste blend. PS was obtained from Belville Wastewater Treatment Works (BWWTW) in Cape Town, while food waste was manually simulated. The augmented biomethane potential (ABMP) experiment was used to obtain the required research data. The ABMP data was used to determine the substrates' biodegradable composition. The biodegradable composition was carried out using two approaches. The first approach is the mass balanced bioprocess stoichiometric calculations, which used the measured start and end concentrations of the ABMP experiment. The second approach is the parameter estimation procedure, which used the mass balanced steady-state AD model of Ikumi et al. (2015) together with its built-in parameter estimation function. With the exception of methane COD produced, there were slight to moderate differences between the measured and modelled experiment results. However, the modelled experiments produced significantly higher methane COD than the measured experiment, suggesting a high-level error associated with the gas measurement. As a result, the modelled experiment and the substrates' composition obtained using parameter estimation were chosen to be more accurate and reliable. The results revealed that anaerobic digestion of food waste and co-digestion of primary sludge and food waste produces 41% and 21% more methane than the anaerobic digestion of primary sludge, respectively. The methane produced is equivalent to the potential energy recoverable. These findings suggest that diverting food waste from landfills to WWTP's AD systems can potentially enhance energy recovery. This highlights the potential need to revise urban wastewater systems to include solid waste separation and food waste diversion to AD systems to enhance resource recovery.